(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study examines the investment behavior of working women in Rajasthan, aiming to understand their preferences, risk appetite, and factors influencing their investment decisions. The research employs a quantitative approach, analyzing data collected from a sample of 200 working women across different cities in Rajasthan. A hypothesis test is conducted to assess the relationship between education level and investment preferences. The findings highlight key trends and provide insights for financial planners and policymakers.